PEMILU SERENTAK 2019 (PROBLEM DAN SOLUSINYA) - Sukawati Lanang Putra Perbawa (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2019)
The General Election (Election) according to some circles is a routine agenda that consumes a lot of budget. This assumption is based on the implementation of elections that have been carried out by the Indonesian nation, which have not yet obtained results in accordance with the wishes of the people. In fact, people assume that the implementation of elections from 1955 to 2019 has not been able to produce a government that is according to the mandate in the 1945 Constitution, namely regarding the objectives of the State.